THE POSSIBLE FUNDAMENTAL EQUATIONS OF THE CONTINUUM MECHANICS - Béda, Gyula (Periodica Polytechnica Mechanical Engineering, 1991)
The possible fundamental equations are looked for in cases of infinitesimal and finite strain based on the investigation of the acceleration wave. It is shown that also the selection of the kinematical equations has an important role besides the constitutive equation.